Is there any effect of symmetry on velocity of the four swimming strokes? - Bartolomeu, Raúl Filipe (2022)
The different characteristics of the four swimming strokes affect the interplay between the four limbs, acting as a constraint to the force produced by each hand and foot. The purpose of this study was to analyze the symmetry of force production with a varying number of limbs in action and see its effect on velocity. Fifteen male swimmers performed four all-out bouts of 25-m swims in the four strokes in full-body stroke and segmental actions. A differential pressure system was used to measure the hands/feet propulsive force and a mechanical velocity meter was used to measure swimming velocity. Symmetry index was calculated based on the force values. All strokes and conditions presented contralateral limb asymmetries (ranging from 6.73% to 28% for the peak force and from 9.3% to 35.7% for the mean force). Backstroke was the most asymmetric stroke, followed-up by butterfly, front crawl, and breaststroke. Kicking conditions elicited the higher asymmetries compared with arm-pull conditions. No significant associations were found between asymmetries and velocity. The absence of such association suggests that, to a certain and unknown extent, swimming may benefit from contralateral limb asymmetry